Enhancing Competitive Advantage in the Disruptive Era: Strategy Formulation Framework in Model Public Junior High Schools in Indonesia - Kamaludin, Kamaludin; Taulany, Himmah; Slamet, Slamet (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to obtain a strategic decision framework through the strategic formulation stages as a solution to the problems found by researchers in implementing strategic formulation at Model Middle Schools in Semarang City. This research uses sequential mixed methods. The data collection techniques used in this research are observation, interviews, questionnaires, and documentation. Triangulation data collection techniques are used to obtain data validity. This research determines strategic planning decisions for Model State Middle Schools in Semarang City, namely service development strategies. The service development strategy is the primary strategy chosen from four existing alternative strategies with strategic actions that can be carried out by Model State Middle Schools in Semarang City, namely developing and establishing service standards, compiling and establishing standard operational procedures, improving the quality of service to the community by tightening supervision through establishing school units and developing a customer complaints system.